مساهمة التجارة الإلكترونية في تنمية التجارة الخارجية - بكريتي بلال, بوبو عيسى (My University, 2022)
This study aims to highlight the role of e-commerce in promoting the freedom of foreign trade across countries, and adding strength in response to the trade relationship from the import and export of goods and services and the movement of capital in a world linked by globalization in the field of technology and communications, through the development of information and communication technology infrastructure In addition to that, the role played by international organizations for their interest in this trade across the world and the enactment of unified and regulating laws for the ideal course in all countries of the world and their systematic application to all countries participating in this trade, this is what gave .value to trade exchange in this way In order to become familiar with the various aspects of the subject and analyze its dimensions, we adopted the descriptive approach that we used as a descriptive account of electronic commerce and its relationship with the World Trade Organization and the legislation governing it, as well as a descriptive and statistical account of the role of .electronic commerce in promoting freedom of foreign trade In this study, various reports have been made on the development of electronic commerce in most countries of the world and the results achieved after working with it, especially the .developed countries whose positive results appeared. across the world
Keywords: e-commerce - forgien Trade-capital movements -global organisations -Trade .exchange